Effect of intra-canal cryotherapy on post-endodontic pain in single-visit RCT: A randomized controlled trial - Abdullah Ahmed Alharthi; Mohammed Hussian Aljoudi; Mulham Naif Almaliki; Majed Abdullah Almalki; Mohammed Abdulwahhab Sunbul (Saudi Dental Journal)
Aim: To evaluate the effect of cold and room-temperature normal saline as a final irrigation on post-endodontic pain and to compare the post-endodontic pain level between the different protocols. Materials and methods: A randomized controlled trial was conducted on 105 patients who underwent RCT and were distributed blindly and randomly into three equal groups (n = 35): Group 1, Cryotherapy group; Group 2, Room- temperature normal saline group; and Group 3, Control group. The patients were asked to fill out the VAS questionnaire and register their post-endodontic pain at 6, 24, and 48 h. One-way analysis of variance (ANOVA) and was used to determine statistical difference (α = 0.05) among the groups. Tuckey’s test was used to calculate P-value (α = 0.05) between two each group. Results: The highest post-endodontic pain was in Group 3. There was no significance difference between Group 1 and Group 2. Conclusion: Final flushing of the canal with saline either cold or at room temperature was effective for post-endodontic pain control. This can be promising as an essential step in endodontic treatment to reduce post-endodontic pain. The room-temperature saline as final irrigation showed comparable results to intra-canal cryotherapy. Keywords: Cryotherapy, Endodontics, Post-operative pain, Single-visit RCT